2015
DOI: 10.1126/sciadv.1500692
|View full text |Cite
|
Sign up to set email alerts
|

Nearly free electrons in a 5 d delafossite oxide metal

Abstract: Transport and ARPES reveal extremely good metallicity arising from almost free-electron behavior in single-crystal PtCoO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
83
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 45 publications
12
83
1
Order By: Relevance
“…A further class of materials recently discovered to have extremely long mean free paths at low temperature are the delafossite oxide metals PdCoO 2 , PtCoO 2 and PdCrO 2 [10,11]. Each can have resistive mean free paths of microns at low temperatures [12][13][14]. Indeed, in the most conductive single crystals of PdCoO 2 , with resistivities as low as 8 nΩcm, mean free paths as long as 20 µm have been reported [15].…”
Section: Introductionmentioning
confidence: 99%
“…A further class of materials recently discovered to have extremely long mean free paths at low temperature are the delafossite oxide metals PdCoO 2 , PtCoO 2 and PdCrO 2 [10,11]. Each can have resistive mean free paths of microns at low temperatures [12][13][14]. Indeed, in the most conductive single crystals of PdCoO 2 , with resistivities as low as 8 nΩcm, mean free paths as long as 20 µm have been reported [15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, depending on the chemical composition, a plethora of behaviors can be evidenced. For instance, for A in a d 9 configuration, e.g., A = Pd or Pt, highly metallic compounds with anomalous temperature dependence of the resistivity have been reported [4][5][6][7]. The transport in these compounds has been found to be strongly anisotropic, with a degree of anisotropy that may reach 1000 [4,5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Several important technological applications have been proposed for members of this family, such as electrodes for hydrogen production by photo-electrochemical water splitting67, as luminescent materials8, in solar cells91011, for thermoelectricity12131415, as possible transparent supercondutors16, etc. Recently, it was also found that delafossite PtCoO 2 behaves like a nearly free-electron system, turning this surprising 5d transition-metal system in the most conductive oxide known17.…”
mentioning
confidence: 99%